2013
DOI: 10.1016/j.neubiorev.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Rats classified as low or high cocaine locomotor responders: A unique model involving striatal dopamine transporters that predicts cocaine addiction-like behaviors

Abstract: Individual differences are a hallmark of drug addiction. Here, we describe a rat model based on differential initial responsiveness to low dose cocaine. Despite similar brain cocaine levels, individual outbred Sprague-Dawley rats exhibit markedly different magnitudes of acute cocaine-induced locomotor activity and, thereby, can be classified as low or high cocaine responders (LCRs or HCRs). LCRs and HCRs differ in drug-induced, but not novelty-associated, hyperactivity. LCRs have higher basal numbers of striat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 126 publications
(307 reference statements)
1
22
0
Order By: Relevance
“…In still other arenas, median splits were used to study the effectiveness of inpatient treatments for pathological gamblers in Germany (Buchner et al, 2014), condom use among men being treated for sexually transmitted diseases (Crosby & Charnigo, 2013), the effect of friendships vs. isolation on patients' perceptions of lower back pain and quality of life (Hawthorne, de Morton, & Kent, 2013), gesture sequences in chimpanzees (McCarthy, Jensvold, & Fouts, 2013), effective measurement of ability and achievement in football, golf, hockey, and other sports (Robertson, Burnett, & Cochrane, 2014), the effect of time and previous injuries to concussion recoveries (Silverberg et al, 2013), cocaine‐induced motor responses in rats (Yamamoto et al, 2013), and the effects of visual stimuli on reaction times and electrophysiological brain activity (Wiebel, Valsecchi, & Gegenfurtner, 2014). In top finance journals, researchers have used median splits to study countries' debt levels and asset values (Kalteier & Posch, 2013), and the effect of venture capital on subsequent corporate financial performance (Hsu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In still other arenas, median splits were used to study the effectiveness of inpatient treatments for pathological gamblers in Germany (Buchner et al, 2014), condom use among men being treated for sexually transmitted diseases (Crosby & Charnigo, 2013), the effect of friendships vs. isolation on patients' perceptions of lower back pain and quality of life (Hawthorne, de Morton, & Kent, 2013), gesture sequences in chimpanzees (McCarthy, Jensvold, & Fouts, 2013), effective measurement of ability and achievement in football, golf, hockey, and other sports (Robertson, Burnett, & Cochrane, 2014), the effect of time and previous injuries to concussion recoveries (Silverberg et al, 2013), cocaine‐induced motor responses in rats (Yamamoto et al, 2013), and the effects of visual stimuli on reaction times and electrophysiological brain activity (Wiebel, Valsecchi, & Gegenfurtner, 2014). In top finance journals, researchers have used median splits to study countries' debt levels and asset values (Kalteier & Posch, 2013), and the effect of venture capital on subsequent corporate financial performance (Hsu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the DAT has also been suggested by studies that have shown that rats showing greater responsiveness to cocaine have higher DAT (27, 28). In the current study, because DAT measurements were made as juveniles, prior to any drug exposure, this could be considered akin to studies of the relationship of genetic variation in the DAT to drug-related cue responding in substance abusers.…”
Section: Discussionmentioning
confidence: 91%
“…Increased DAT surface expression could reflect differential activation of proteins that regulate DAT trafficking, including PKCβ (Chen et al ., ). In addition, STs and GTs could also differ in movement of DAT into and out of the membrane after administration of AMPH (Johnson et al ., ; Yamamoto et al ., ). However, a single AMPH injection does not alter the maximal rate of DA uptake ( V max , a measure of DAT expression) within 1 h of administration (Ferris et al ., ).…”
Section: Discussionmentioning
confidence: 97%